Genome-wide association and genomic prediction for scrotal circumference in Hereford and Braford bulls - Ferreira, Carlos E.R.; Campos, Gabriel S.; Schmidt, Patricia I. [UNESP]; Sollero, Bruna P.; Goularte, Karina L.; Corcini, Carine D.; Gasperin, Bernardo G.; Lucia, Thomaz; Boligon, Arione A.; Cardoso, Fernando F. (Elsevier, 2021)
Scrotal circumference (SC) is widely used as a selection criterion for bulls in breeding programs, since it is easily assessed and correlated with several desirable reproductive traits. The objectives of this study were: to perform a genome-wide association study (GWAS) to identify genomic regions associated with SC adjusted for age (SCa) and for both age and weight (SCaw); to select Tag SNPs from GWAS to construct low-density panel for genomic prediction; and to compare the prediction accuracy of the SC through different methods for Braford and Hereford bulls from the same genetic breeding program. Data of SC from 18,172 bulls (30.4 ± 3.7 cm) and of genotypes from 131 sires and 3,545 animals were used. From GWAS, the top 1% of 1-Mb windows were observed on chromosome (BTA) 2, 20, 7, 8, 15, 3, 16, 27, 6 and 8 for SCa and on BTA 8, 15, 16, 21, 19, 2, 6, 5 and 10 for SCaw, representing 17.4% and 18.8% of the additive genetic variance of SCa and SCaw, respectively. The MeSH analysis was able to translate genomic information providing biological meanings of more specific gene functions related to the SCa and SCaw. The genomic enhancement methods, especially single step GBLUP, that combined phenotype and pedigree data with direct genomic values generated gains in accuracy in relation to pedigree BLUP, suggesting that genomic predictions should be applied to improve genetic gain and to narrow the generation interval compared to traditional methods. The proposed Tag-SNP panels may be useful for lower-cost commercial genomic prediction applications in the future, when the number of bulls in the reference population increases for SC in Hereford and Braford breeds.
Keywords: Beef cattle; GWAS; Low-density panel; Prediction accuracy; Reproductive performance